Code Mixing Used by Niki Zefanya in Najwa Shihab’s Youtube Channel - Ni Komang Trisna Arisedani; I Gusti Ayu Vina Widiadnya Putri (RETORIKA: Jurnal Ilmu Bahasa, 2024)
This study explores the phenomenon of code-mixing as observed in the discourse of Niki Zefanya on Najwa Shihab's YouTube channel, utilizing the theoretical frameworks proposed by Muysken (2000) and Hoffman. The aim is to elucidate Niki Zefanya's motivations behind code-mixing in this context. Through a descriptive qualitative approach, the research delves into code-mixing practices on social media platforms, particularly YouTube, seeking to deepen our understanding of this linguistic phenomenon. Data collection involved meticulous observation and note-taking during the YouTube video "Eksklusif: Apa Adanya Rich Brian & NIKI | Mata Najwa" hosted by Najwa Shihab, focusing on Niki Zefanya's linguistic expressions. The analysis employed a combination of formal and informal methods. The findings highlighted 7 instances of insertion, 6 of alternation, and 8 of congruent lexicalization, showcasing the diverse manifestations of code-mixing. These insights contribute to our understanding of language use in online content, particularly in the realm of sociolinguistics. This study also reflects on the broader implications of the findings for sociolinguistic research, considering the significance of code-mixing in contemporary digital communication. Understanding these implications could offer valuable insights for future research endeavors in sociolinguistics.